2020 IEEE 44th Annual Computers, Software, and Applications Conference (COMPSAC) 2020
DOI: 10.1109/compsac48688.2020.00020
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Systems Modelling with Adaptive Traffic Profiles and Its Application to Worst-Case Analysis of a DRAM Controller

Abstract: Computing Systems are evolving towards more complex, heterogeneous systems where multiple computing cores and accelerators on the same system concur to improve computing resources utilization, resources re-use and the efficiency of data sharing across workloads. Such complex systems require equally complex tools and models to design and engineer them so that their use-case requirements can be satisfied. Adaptive Traffic Profiles (ATP) introduce a fast prototyping technology, which allows one to model the dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…A First-Ready, First-Come-First-Served (FR-FCFS) DRAM controller is chosen as an example to show how to compute a service curve for a read request arriving at the latter. To do so, first an upper bound on its WCD [14] is computed. Furthermore, it is shown that this upper bound is not overly pessimistic by computing a lower bound too and that the gap between the upper and lower bound is null to negligible in practical cases.…”
Section: A Worst-case Analysis Of a Fr-fcfs Dram Controllermentioning
confidence: 99%
“…A First-Ready, First-Come-First-Served (FR-FCFS) DRAM controller is chosen as an example to show how to compute a service curve for a read request arriving at the latter. To do so, first an upper bound on its WCD [14] is computed. Furthermore, it is shown that this upper bound is not overly pessimistic by computing a lower bound too and that the gap between the upper and lower bound is null to negligible in practical cases.…”
Section: A Worst-case Analysis Of a Fr-fcfs Dram Controllermentioning
confidence: 99%
“…The latter is a theory for deterministic network evaluation, which dates back to the early 1990s, and it is mainly due to the work of Cruz [7], [8], Le Boudec and Thiran [9], and Chang [10]. Originally devised for the Internet, where it was used to engineer models of service [11]- [15], it has found applications in several other contexts, from sensor networks [16] to avionic networks [17], [18], industrial networks [19]- [21], automotive systems [22] and systems architecture [23], [24]. Its main strength is that it allows one to compute worst-case delay bounds in systems with multi-hop traversal.…”
Section: Introductionmentioning
confidence: 99%
“…NC dates back to the early 1990s, and it is mainly due to the work of Cruz [1,2], Le Boudec and Thiran [3], and Chang [4]. Originally devised for the Internet, where it was used to engineer models of service [5][6][7][8][9], it has found applications in several other contexts, from sensor networks [10] to avionic networks [11,12], industrial networks [13][14][15] automotive systems [16] and systems architecture [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Extending the NC Algorithmic Toolbox for UPP Functions bits Fig. 1: Example of leaky-bucket shaper, taken from [17]. The traffic process A(t) is always below the arrival curve α(t) and its translations along A(t).…”
Section: Introductionmentioning
confidence: 99%